2022
DOI: 10.1038/s41418-022-00974-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Drp1 promotes fatty acids-induced metabolic reprograming to potentiate Wnt signaling in colon cancer

Abstract: Cancer cells are known for their ability to adapt variable metabolic programs depending on the availability of specific nutrients. Our previous studies have shown that uptake of fatty acids alters cellular metabolic pathways in colon cancer cells to favor fatty acid oxidation. Here, we show that fatty acids activate Drp1 to promote metabolic plasticity in cancer cells. Uptake of fatty acids (FAs) induces mitochondrial fragmentation by promoting ERK-dependent phosphorylation of Drp1 at the S616 site. This incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 50 publications
4
28
0
Order By: Relevance
“…Interestingly, we could demonstrate secretion of the modified DRP-1 forms to the media and inter-cellular transfer of the pDRP-1 (S616) deposits from one astrocyte to another via TNTs and thicker protrusions. In line with our findings, a recent study suggests an integral role of DRP-1 in fatty acid β oxidation [ 40 ]. The authors demonstrated that DRP-1 knock-out cell line translocate LDs to their mitochondria, but have a decreased fatty acid degradation.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we could demonstrate secretion of the modified DRP-1 forms to the media and inter-cellular transfer of the pDRP-1 (S616) deposits from one astrocyte to another via TNTs and thicker protrusions. In line with our findings, a recent study suggests an integral role of DRP-1 in fatty acid β oxidation [ 40 ]. The authors demonstrated that DRP-1 knock-out cell line translocate LDs to their mitochondria, but have a decreased fatty acid degradation.…”
Section: Discussionsupporting
confidence: 93%
“…Zhang et al [ 86 ] demonstrated that the Wnt/β-Catenin signaling pathway was promoted by Ribonuclease H1 antisense RNA 1 in lung cancer tissue and in non-small cell lung cancer (NSCLC) cell lines. In addition, PT130 cells and tumor organoid culture studies assumed that activation of dynamin-related protein 1 (Drp1) promotes fatty acid-induced metabolic reprogramming to enhance Wnt signaling in colon cancer [ 87 ]. Recently, Sana et al [ 88 ] were able to show that vitamin deficiency as well as the expression of VDR and retinoid X receptor (RXR) correlated with blood cancer diagnosis in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Activated Drp1 changes the metabolic pathway, facilitates the oxidation of fatty acids, and promotes the proliferation of colon cancer cells. 176 …”
Section: Phosphorylationmentioning
confidence: 99%
“…The kinase ERK catalyzes Drp1 phosphorylation at Ser616 to activate Drp1. Activated Drp1 changes the metabolic pathway, facilitates the oxidation of fatty acids, and promotes the proliferation of colon cancer cells 176 …”
Section: Phosphorylationmentioning
confidence: 99%